Long-range transported North American wildfire aerosols observed in marine boundary layer of eastern North Atlantic. (June 2020) - Zheng, Guangjie; Sedlacek, Arthur J.; Aiken, Allison C.; Feng, Yan; Watson, Thomas B.; Raveh-Rubin, Shira; Uin, Janek; Lewis, Ernie R.; Wang, Jian
Highlights: Well-aged Canadian wildfire aerosols observed in marine boundary layer over the Azores. Dry intrusions accelerate the descent of wildfire aerosols into marine boundary layer. Optical properties of aged wildfire aerosols suggest nearly complete loss of brown carbon. Aged wildfire aerosols contribute efficiently to CCN population for marine low clouds. Abstract: Wildfire is a major source of biomass burning aerosols, which greatly impact Earth climate. Tree species in North America (NA) boreal forests can support high-intensity crown fires, resulting in elevated injection height and longer lifetime (on the order of months) of the wildfire aerosols. Given the long lifetime, the properties of aged NA wildfire aerosols are required to understand and quantify their effects on radiation and climate. Here we present comprehensive characterization of climatically relevant properties, including optical properties and cloud condensation nuclei (CCN) activities of aged NA wildfire aerosols, emitted from the record-breaking Canadian wildfires in August 2017. Despite the extreme injection height of ~12 km, some of the wildfire plumes descended into the marine boundary layer in the eastern North Atlantic over a period of ~2 weeks, owing to the dry intrusions behind mid-latitude cyclones. The aged wildfire aerosols have high single scattering albedos at 529 nm (ω529 ; 0.92–0.95) while low absorption Ångström exponents (Åabs ) at 464 nm/648 nm (0.7–0.9). In comparison, Åabs of fresh/slightly aged ones are typically 1.4–3.5. This low Åabs indicates a nearly complete loss of brown carbon, likely due to bleaching and/or evaporation, during the long-range transport. The nearly complete loss suggests that on global average, direct radiative forcing of BrC may be minor. Combining Mie calculations and the measured aerosol hygroscopicity, volatility and size distributions, we show that the high ω529 and low Åabs values are best explained by an external mixture of non-absorbing organic particles and absorbing particles of large BC cores (>~110 nm diameter) with thick non-absorbing coatings. The accelerated descent of the wildfire plume also led to strong increase of CCN concentration at the supersaturation levels representative of marine low clouds. The hygroscopicity parameter, κ CCN, of the aged wildfire aerosols varies from 0.2 to 0.4, substantially lower than that of background marine boundary layer aerosols. However, the high fraction of particles with large diameter (i.e., within accumulation size ranges, ~100–250 nm) compensates for the low values of κ, and as a result, the aged NA wildfire aerosols contribute more efficiently to CCN population. These results provide direct evidence that the long-range transported NA wildfires can strongly influence CCN concentration in remote marine boundary layer, therefore the radiative properties of marine low clouds. Given the expected increases of NA wildfire intensity and frequency and regular occurrence of dry intrusion following mid-latitude cyclones, the influence of NA wildfire aerosols on CCN and clouds in remote marine environment need to be further examined.